“Shifting in” migration control Universalism and immigration in Costa Rica - Voorend, Koen (2013)
When the Caja Costarricense de Seguro Social (CCSS), the flagship institution of Costa Rica’s ‘exceptional’ -solidary and universal- social policy regime, entered in financial crisis in 2011, the already difficult social integration of Nicaraguan immigrants in Costa Rica became even more critical. Faced with a general deterioration of social services, a perception that immigrants are threatening the availability of jobs and social services for the national population, and voices that advocate the creation of limits to social rights and access to social benefits, this essay analyzes the political reaction of the State, specifically whether it chooses to limit immigrants’ access to healthcare. In a discussion on state sovereignty, universalism and social rights, this article argues that immigration control responsibilities are transferred to social policy institutions, “shifting in” migration control and that the principle of universalism of Costa Rica’s social policy regime does not necessarily apply to parts of the immigrant population, both irregular and regular.